Supplier Data Analysis and Utilization in Supply Chain Management : Case ABB Smart Power - Hahto, Miika (My University, 2023)
This thesis' subject is utilizing supplier data analysis for supply chain management at ABB Smart Power. The research problem is the lack of information on the supply chain. Suppliers and materials are divided into three categories based on their relationship to the supply chain. The main information to be learned from this data is material consumption, material spend, material volume, and movement of materials in the supplier network. The Purpose of this thesis is to build a supply data analysis system to calculate and visualize this information for the supply chain management team. This thesis excludes electronic components due to their volatility in the market. In addition, machine learning algorithm k-nearest neighbours is tested for material price forecasting. The thesis focuses on the research question “how can the program Power BI be used for gathering, analysing, and utilizing the supplier data”. The solution proposed is to automate supplier data extraction from SAP ERP utilizing Microsoft Excel with VBA-programming and utilize Microsoft Power BI for data analysis, visualization, and machine learning to provide the information required to solve the research problem. The Development process for the solution to the research problem can be divided into four parts which are data extraction, data analysis, visualization and utilization, and machine learning. This solution is built through multiple prototypes and developed based on theory, testing, and feedback. The end product is released to Power BI Service ABB workspace for use. The thesis is divided into seven chapters according to the constructive research process steps. The first three chapters focus on the background, research question, theory, and technologies utilized in the thesis. The fourth chapter focuses on the research approach and process. The fifth chapter focuses on the solution construct’s development process and the sixth chapter on the results of this solution. The final chapter focuses on the conclusions, discussion, and future development of this research. The development and results of this thesis conclude that the combination of Microsoft Excel with VBA-programming and Microsoft Power BI for data analysis presents an efficient method for gathering, analysing, and utilizing supplier data. Through the data analysis capabilities of Power BI, the data can be analysed, calculated, and visualized efficiently. The Machine learning implementation is possible for Power BI, however utilizing DAX-programming caused technical problems which could not be solved during the thesis.

Tämän tutkielman aiheena on toimittajadatan käyttö ja analysointi toimitusketjun hallinnassa ABB Smart Powerilla. Tutkimusongelma on toimittajatiedon puute toimitusketjussa. Toimittajat ja materiaalit on jaettu kolmeen kategoriaan perustuen toimitusketju suhteisiin. Tärkeimmät hyödynnettävät tiedot tästä datasta ovat materiaalien kulutus, materiaalikulut, materiaalimäärät ja materiaalien liikkuminen toimittajaverkostossa. Tämän tutkielman päämääränä on rakentaa järjestelmä toimittajadatan analysoimiseen, laskemiseen sekä visualisointiin toimitusketjun hallintatiimille. Tutkielma poissulkee elektroniset komponentit, johtuen niiden markkinoiden epävakaudesta. Lisäksi koneoppimisalgoritmi k-nearest neighboursia testataan materiaalien hintojen ennustamiseen. Tutkielma keskittyy tutkimuskysymykseen “Kuinka Power BI ohjelmaa voidaan hyödyntää toimittajadatan keräämiseen, analysointiin ja käyttöön”. Ehdotettu ratkaisu on automatisoida toimittajadatan keräys käyttämällä Microsoftin Excel-ohjelmaa VBA-ohjelmoinnin kanssa ja käyttää Microsoft Power BI:tä datan analysointiin, visualisointiin sekä koneoppimiseen tarvittavan informaation saamiseen tutkimuskysymyksen ratkaisemiseksi. Ratkaisun kehitysprosessi voidaan jakaa neljään osaan, jotka ovat datan keräys, data-analyysi, visualisointi ja koneoppiminen. Ratkaisu rakennetaan prototyyppien kautta, jotka kehittyvät teorian, testauksen ja palautteen perusteella. Lopputuote julkaistaan Power BI Servicessa ABB:n workspacessa. Tutkielma on jaettu seitsemään osaan konstruktiivisen tutkimuksen vaiheiden mukaisesti. Ensimmäiset kolme kappaletta keskittyvät taustatietoihin, tutkimuskysymykseen, teoriaan sekä käytettyihin teknologioihin. Neljäs kappale keskittyy tutkimuksen lähestymistapaan sekä prosessiin. Viides kappale keskittyy ratkaisun konstruktion kehitysprosessiin ja kuudes kappale keskittyy tämän ratkaisun tuloksiin. Viimeinen kappale keskittyy lopputuloksiin, pohdintaan sekä kehitykseen. Tutkielman kehityksen ja tuloksien perusteella VBA-ohjelmoinnin käyttö Microsoft Excel ohjelmoinnilla yhdistettynä Power BI:n data analyysin kanssa tuottaa tehokkaan metodin toimittajadatan keräämiseen, analysointiin sekä käyttöön. Power BI:n data-analyysiominaisuuksien avulla data voidaan tehokkaasti analysoida, laskea ja visualisoida. DAX-ohjelmoinnin hyödyntäminen koneoppimisessa aiheutti toisaalta teknisiä ongelmia, joita ei pystytty ratkaisemaan tässä tutkielmassa.
Keywords: supply chains; machine learning; logistics; automation; visualisation; data systems; acquisition; information (data); fi=Automaatio- ja tietotekniikka|en=Automation and Computer Science|; fi=Energia- ja informaatiotekniikan ohjelma|en=Degree Programme in Energy Technology and Information Technology|